Estudo da continuidade em ligações laje-viga-pilar em estruturas pré-moldadas de concreto - Kataoka, Marcela Novischi (2007)
The present research deals with the study of continuity in slab-beam-column connections in precast concrete structures, wherein an experimental investigation about the contribution of longitudinal reinforced bars, passing on the side of the column in the top of the slab, on the connector flexural stiffness. For this study, a beam-to-column connection was selected, comprising concrete corbel with dowel bars and continuity reinforced bars passing trough the column and fulfilling of grout in the interface of the connection. Two tests were carried out for the characterization of the moment-rotation relationship of two different connection prototypes, one with 100% of the continuity reinforced bars passing trough the column and another with 50% trough the column and 50% in the laterals. The experimental results indicate that bars passing on both sides of the column enhanced the moment-rotation relationship for the second prototype, being even more significant for the serviceability stage. However, rotations at the beginning of plasticization of the moment-rotation curve were close for the two prototypes. The results indicate that the transverse reinforcement between the slab and the beam was capable of mobilizing the external longitudinal bars at the same time of the internal longitudinal bars, passing through the column. Additionally, this reinforcement arrangement provided an increase of the cracking control within the connection zone at the end of the beam